The PRISMA 2020 statement: An updated guideline for reporting systematic reviews - Page, Matthew J.; McKenzie, Joanne E.; Bossuyt, Patrick M.; Boutron, Isabelle; Hoffmann, Tammy C.; Mulrow, Cynthia D.; Shamseer, Larissa; Tetzlaff, Jennifer M.; Akl, Elie A.; Brennan, Sue E.; Chou, Roger; Glanville, Julie; et al. (Journal of clinical epidemiology, 2021)
The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement, published in 2009, was designed to help systematic reviewers transparently report why the review was done, what the authors did, and what they found. Over the past decade, advances in systematic review methodology and terminology have necessitated an update to the guideline. The PRISMA 2020 statement replaces the 2009 statement and includes new reporting guidance that reflects advances in methods to identify, select, appraise, and synthesise studies. The structure and presentation of the items have been modified to facilitate implementation. In this article, we present the PRISMA 2020 27-item checklist, an expanded checklist that details reporting recommendations for each item, the PRISMA 2020 abstract checklist, and the revised flow diagrams for original and updated reviews.